2018
DOI: 10.1186/s42358-018-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in rheumatoid arthritis

Abstract: Rheumatoid arthritis affects millions of people worldwide and is considered a chronic multisystem disease whose causes are unknown. In general, the main objective of rheumatoid arthritis treatment is to improve the quality of life of patients by relieving pain, maintaining or improving functional capacity, preventing thus, disability. In recent years the role of adipokines in the pathogenesis of rheumatoid arthritis has been discussed but results are still conflicting. Although results from some studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 67 publications
1
80
0
9
Order By: Relevance
“…Other receptors such as T cadherin [57,58,59,60] and PAQR3 [61] have also been discussed. Mainly anti-inflammatory effects at the systemic level have been described for adiponectin in atherosclerosis but also for example in metabolic syndrome, type 2 diabetes mellitus [56,62]. In contrast, adiponectin seems to have opposing effects on effector cells of arthritis.…”
Section: Adiponectinmentioning
confidence: 99%
See 2 more Smart Citations
“…Other receptors such as T cadherin [57,58,59,60] and PAQR3 [61] have also been discussed. Mainly anti-inflammatory effects at the systemic level have been described for adiponectin in atherosclerosis but also for example in metabolic syndrome, type 2 diabetes mellitus [56,62]. In contrast, adiponectin seems to have opposing effects on effector cells of arthritis.…”
Section: Adiponectinmentioning
confidence: 99%
“…Numerous studies found that cultured RASF respond to adiponectin by an increase of pro-inflammatory factors including prostaglandin E2, IL-6, IL-8, MMPs-1, -13 [56,62]. However, a stronger pro-inflammatory effect of the HMW isoforms has been described in contrast to LMW adiponectin in these cells [56,62]. For some cell types, even opposing effects have been described for specific adiponectin isoforms.…”
Section: Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, plasma adiponectin levels have been associated with circulating inflammatory cytokines in a cohort of subjects at high risk to develop RA (20). Taken all together, those results suggest that adiponectin might be a factor implicated in the initiation and progression of RA (21).…”
Section: Introductionmentioning
confidence: 70%
“…Several biological mechanisms have been proposed to interpret the potential effect of resistin on the pathogenesis of RA. It is widely recognized that RA is a persistent in ammatory diease, which is related to several in ammatory cytokines [39]. Šenolt et al reported that resistin was expressed in different in ammatory cells of RA synovial tissue, including macrophages (CD68), B lymphocytes (CD20) and plasma cells (CD138) [40].…”
Section: Discussionmentioning
confidence: 99%